2008
DOI: 10.1021/jm800510m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of [N-methyl-11C]N-Desmethyl-loperamide as a New and Improved PET Radiotracer for Imaging P-gp Function

Abstract: Abstract[ 11 C]Loperamide has been proposed for imaging P-glycoprotein (P-gp) function with positron emission tomography (PET), but its metabolism to [N-methyl-11 C]N-desmethyl-loperamide ([ 11 C] dLop; [ 11 C]3) precludes quantification. We considered that [ 11 C]3 might itself be a superior radiotracer for imaging brain P-gp function and therefore aimed to prepare [ 11 C]3 and characterize its efficacy. An amide precursor (2) was synthesized and methylated with [ 11 C]iodomethane to give [ 11 C]3. After adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
103
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 34 publications
4
103
0
Order By: Relevance
“…The radiopharmaceutical was obtained with high radiochemical purity (93% 6 3%), chemical purity (.95%), and specific activity (571.23 6 130.8 GBq/mmol), which are consistent with prior reports from our institution (15) and others (16) where similar synthetic N-11 C methylation schemes of the amide precursors have been used.…”
Section: Radiosynthesissupporting
confidence: 80%
“…The radiopharmaceutical was obtained with high radiochemical purity (93% 6 3%), chemical purity (.95%), and specific activity (571.23 6 130.8 GBq/mmol), which are consistent with prior reports from our institution (15) and others (16) where similar synthetic N-11 C methylation schemes of the amide precursors have been used.…”
Section: Radiosynthesissupporting
confidence: 80%
“…14 Di-desmethyl-loperamide (2) as precursor for [ 11 C]-labeling was prepared according to the literature method (Lazarova et al, 2008) consisting in alkylating 4-(4-chlorophenyl)-4-hydroxypiperidine with 4-bromo-2,2-diphenylbutyronitrile to obtain nitrile 1 which was subsequently hydrolyzed with sodium hydroxide to lead to precursor 2 (di-dLop) with a good overall yield. Direct methylation of di-dLop (2) seemed the shortest way to provide Ndesmethyl-loperamide (dLop) but was reported to be very low yielding (3 %) using methyl iodide as alkylating agent and potassium hydroxide as a base (Lazarova et al, 2008).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In drug development, the use of PET in combination with [ 11 C]dLop may be an appealing approach for the non-invasive study of the potency of new chemical entities to inhibit P-gp function at the BBB (Wulkersdorfer et al, 2014). The radiosynthesis and initial pharmacological evaluation of [ 11 C]dLop have been proposed by Lazarova et al (2008). An optimized preparation of [ 11 C]dLop to facilitate its use in preclinical and clinical PET studies has been reported (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, 11 C-verapamil radiometabolites complicate PET data analysis because some of these radiometabolites can freely cross the BBB, whereas others interact with P-gp (4). 11 C-N-desmethyl-loperamide, which is a metabolite of loperamide, is another avid P-gp substrate with improved metabolic stability in vivo (5). These specific PET radiotracers have shown that P-gp restricts the brain uptake (K 1 ; influx rate constant) of its substrates, thus limiting their exposure to the brain (6).…”
mentioning
confidence: 99%